2013
DOI: 10.1016/j.ygyno.2013.04.292
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities and patterns of ovarian cancer surgical care in California

Abstract: Objective-To investigate disparities in the frequency of ovarian cancer-related surgical procedures and access to high-volume surgical providers among women undergoing initial surgery for ovarian cancer according to race. Methods-TheCalifornia Office of Statewide Health Planning and Development database was accessed for women undergoing a surgical procedure that included oophorectomy for a malignant ovarian neoplasm between 1/1/06 and 12/31/10. Multivariate logistic regression analyses were used to evaluate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It should be reiterated that both these studies did not stratify by HPV+ OPSCC 19 , 32 . Multiple other studies confirm that racial disparity in treatment extends beyond HNC 21,33–36 . For example, while evaluating treatment for esophageal cancer, Savitch et al established that Black race was associated with lower likelihood of receiving surgery across all cancer stages 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be reiterated that both these studies did not stratify by HPV+ OPSCC 19 , 32 . Multiple other studies confirm that racial disparity in treatment extends beyond HNC 21,33–36 . For example, while evaluating treatment for esophageal cancer, Savitch et al established that Black race was associated with lower likelihood of receiving surgery across all cancer stages 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that sociodemographic factors may influence the oncologic treatment that patients ultimately receive 17 , 18 . Specifically, patient race affects both the likelihood and the timing of receiving surgery for a variety of cancers, with Black individuals being less likely to receive surgery for head and neck, ovarian, breast, and pituitary carincoma 17–21 . Other studies have reported that health insurance coverage may influence the likelihood of receiving indicated cancer surgery, with uninsured and Medicaid patients being significantly less likely to receive definitive surgical treatment for HNC 17,22,23 .…”
mentioning
confidence: 99%
“…15 Multiple prior studies have shown that NHB race is associated with inequity in treatment, including delays in chemotherapy initiation and decreased rates of surgical staging. 3,6,7,16,17 Recently, Dilley et al showed that NHB race was also associated with higher medical comorbidities and lower rates of optimal cytoreduction. 18 In that study, after controlling for age, stage, medical comorbidities and suboptimal cytoreduction, NHB was still associated with worse survival, though they did not account for socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that black women were less likely than white women to receive guideline-recommended care, and women who did not receive recommended treatment had lower survival rates than women who received recommended care [17]. Specifically, Liu FW et al confirmed that black patients were significantly less likely to undergo important ovarian cancer-specific surgical procedures compared to white patients [18].…”
Section: Discussionmentioning
confidence: 99%